Facing yourself in a virtual reality-assisted perspective-taking intervention: an interpretative phenomenological analysis - Sairanen, Essi; Wallsten, Daniel (Frontiers in Psychology, 2025)
IntroductionPeople's self-narratives—how they relate to themselves and others—are closely intertwined with psychological suffering and wellbeing. This study investigates a perspective-taking intervention rooted in Relational Frame Theory (RFT), where participants observe themselves from an outside perspective in Virtual Reality (VR).MethodsThree participants watched 3D-filmed versions of themselves through a VR headset while reflecting on perspective-taking questions. Semi-structured interviews were conducted, and the transcripts were analyzed using Interpretative Phenomenological Analysis (IPA).ResultsThe intervention helped participants become more aware of their self-relating. They recognized how they internalized perceived judgments from others and how they adjusted their behavior accordingly. Self-critical tendencies and the double standards they applied to themselves vs. others became more apparent, often evoking self-compassion. The intervention also revealed discrepancies between participants' internal and external views—that is, how they perceived themselves from the inside vs. the outside.DiscussionThese findings highlight the promising therapeutic potential of this intervention, both for assessing and influencing self-relating.